ENDOSCOPIC SUBMUCOSAL DISSECTION FOR GASTRIC SUBMUCOSAL TUMOR, ENDOSCOPIC SUB-TUMORAL DISSECTION - Hoteya, Shu; Iizuka, Toshiro; Kikuchi, Daisuke; Yahagi, Naohisa (Digestive endoscopy, 2009)
Gastric submucosal tumor (SMT) is frequently found during screening endoscopy, but definitive diagnosis based on histological confirmation is relatively difficult. Even without accurate diagnosis before treatment, open or laparoscopic surgery is currently carried out to remove SMT. The purpose of this study was to demonstrate the feasibility of endoscopic submucosal dissection (ESD) in diagnostic treatment for submucosal tumor (SMT) of the stomach. Subjects in this case study comprised nine patients who had undergone ESD for gastric SMT. Before treatment, endoscopic ultrasonography was carried out in all cases to evaluate depth and origin of the SMT. Then ESD was only indicated for tumors of submucosal layer or muscularis mucosa origin. Using an endoscopic sub‐tumoral dissection technique with a hook knife and a flex knife, local complete resections were achieved in all patients without severe complications. These results suggest the clinical benefits of ESD avoiding oversurgery for the diagnostic treatment of gastric SMT of the submucosal layer and muscularis mucosa origin.